Objective measurement of attention deficit hyperactivity disorder symptoms outside the clinic using the QbCheck: Reliability and validity. Issue 2 (25th February 2020) - Ulberstad, Fredrik; Boström, Hans; Chavanon, Mira‐Lynn; Knollmann, Martin; Wiley, James; Christiansen, Hanna; Thorell, Lisa B.
Abstract: Objective measurements of ADHD symptom levels can be a highly valuable complement to ratings. However, sometimes it is not feasible to bring patients into the clinic/lab for assessment. The aim of the present study was therefore to evaluate the psychometric properties of the QbCheck, an online computerized test that measures errors and reaction time as well as activity during testing using the computer's built‐in web camera. Study I ( n = 27 adolescents/adults) investigated test–retest reliability and concurrent validity of the QbCheck. Study II included 142 adolescents/adults (69 with ADHD/73 controls) and investigated convergent and diagnostic validity, as well as usability, of the QbCheck. In Study I, the QbCheck showed high test–retest reliability and high concurrent validity. In Study II, high convergent validity was observed when studying associations between the QbCheck performed in the home and the QbTest performed at the clinic. In addition, the QbCheck discriminated well between patients with ADHD and controls, with a sensitivity of 82.6 and a specificity of 79.5. The QbCheck appears to be a valuable test with good psychometric properties and will thereby enable assessment of ADHD symptom levels in adolescents and adults outside the clinic in the home setting.